PRDM1 Drives Human Primary T Cell Hyporesponsiveness by Altering the T Cell Transcriptome and Epigenome - Guo, Huidong; Wang, Ming; Wang, Bixia; Guo, Liping; Cheng, Yifei; Wang, Zhidong; Sun, Yu-Qian; Wang, Yu; Chang, Ying-Jun; Huang, Xiao-Jun (Frontiers in Immunology, 2022)
T cell hyporesponsiveness is crucial for the functional immune system and prevents the damage induced by alloreactive T cells in autoimmune pathology and transplantation. Here, we found low expression of PRDM1 in T cells from donor and recipients both related to the occurrence of aGVHD. Our systematic multiomics analysis found that the transcription factor PRDM1 acts as a master regulator during induced human primary T cell hyporesponsiveness. PRDM1-overexpression in primary T cells expanded Treg cell subset and increased the expression level of FOXP3, while decreased expression had the opposite effects. Moreover, the binding motifs of key T cell function regulators, such as FOS, JUN and AP-1, were enriched in PRDM1 binding sites and that PRDM1 altered the chromatin accessibility of these regions. Multiomics analysis showed that PRDM1 directly upregulated T cell inhibitory genes such as CD244, KLF2 and KLRD1 and downregulated the T cell activation gene IL2, indicating that PRDM1 could promote a tolerant transcriptional profile. Further analysis showed that PRDM1 upregulated FOXP3 expression level directly by binding to FOXP3 upstream enhancer region and indirectly by upregulating KLF2. These results indicated that PRDM1 is sufficient for inducing human primary T cell hyporesponsiveness by transcriptomic and epigenetic manners.